Business Process Maturity A Comparative Study on a Sample of Business Process Maturity Models - Van Looy, Amy.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Organisations face many challenges, which induce them to perform better, and thus to establish mature (or excellent) business processes. As they now face globalisation, higher competitiveness, demanding customers, growing IT possibilities, compliancy rules, etc., business process maturity models (BPMMs) have been introduced to help organisations gradually assess and improve their business processes (e.g. CMMI or OMG-BPMM). In fact, there are now so many BPMMs to choose from that organisations risk selecting one that does not fit their needs, or one of substandard quality. This book presents a study that distinguishes process management from process orientation so as to arrive at a common understanding. It also includes a classification study to identify the capability areas and maturity types of 69 existing BPMMs, in order to strengthen the basis of available BPMMs. Lastly it presents a selection study to identify criteria for choosing one BPMM from the broad selection, which produced a free online selection tool, BPMM Smart-Selector.
1. Introduction -- 2. Research -- 3.Conclusions.
Keywords: Economics; Operations research; Management information systems; Economics/Management Science; Business Information Systems; Organizational Studies, Economic Sociology; Operation Research/Decision Theory; Continuous Optimization